Asuhan Kebidanan Komprehensif pada Ny. N Usia 22 Tahun G1P0A0 di Desa Jatirunggo Pringapus - Dewianti, Azelia; Vistra Veftisia (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2024)
The period of pregnancy, childbirth, postpartum, neonate is a physiologic condition that can threaten the safety of the life of the mother and baby and can even cause death. One effort that can be made is to implement a comprehensive midwifery care mode to optimize the detection of high risk maternal neonates. The aim of Comprehensive Midwifery Care (CoC) for Mrs N is to provide midwifery care for pregnant women, giving birth, postpartum, BBL and family planning for Mrs N G1P0A0 The method used in this comprehensive care case study research for pregnant, maternity, newborn and postpartum women is a descriptive method. The type of descriptive research used was case study. The sample in this study was a pregnant woman in the second trimester, 27 weeks gestation, G1P0A0. Research time 20 June 2024 - 25 October 2024 in the Jatirunggu Village area RT 04/RW03. The research instrument uses the SOAP documentation method. Collection of subjective data on Mrs. Assessment of Mrs. So that no gaps were found. Management of comprehensive midwifery care was carried out in accordance with Mrs. N's needs so that no gaps were found between theory and cases. Documentation of comprehensive midwifery care has been carried out in accordance with SOAP managementThe still high maternal and infant mortality rate means that Continuity of Care (COC)-based midwifery care is needed, starting from pregnant women, giving birth, postpartum, neonates and family planning. Midwifery services should be provided from preconception, early pregnancy, during all trimesters, labor and delivery through the first six weeks postpartum Research methods. The methods used in continuous care for Mrs.  N starting from pregnancy care, maternity, postpartum, newborn care and family planning is a descriptive method. The type of final assignment report used is a case study. Within June – September 2024. Collection technique using interviews and observation. Research result Collection of subjective data on Mrs. The assessment of Mrs. N's objective data starting from pregnancy, childbirth, newborns, neonates and the postpartum period has been carried out, there is no gap between theory and cases. Analysis of the data obtained is in accordance with the care provided so that it can be used as a diagnostic enforcer. So no gaps were found. Management of comprehensive midwifery care has been carried out in accordance with Mrs. N's needs so that there are no gaps between theory and cases. Documentation of comprehensive midwifery care has been carried out in accordance with SOAP management   Abstrak Masa kehamilan, persalinan, nifas, neonatus merupakan suatu keadaan fisioligis yang dapat mengancam keselamatan jiwa ibu dan bayi bahkan dapat menyebabkan kematian. Salah satu upaya yang dapat dilakuan dengan menerapkan mode asuha kebidanan komprehensif untuk mengoptimalkan deteksi resiko tinggi maternal neonatal. Tujuan Asuhan Kebidanan Komperhensif (CoC) pada Ny N untuk melakukan asuhan kebidanan pada ibu hamil,bersalin,nifas,BBL dan KB pada Ny N G1P0A0 Metode yang digunakan pada penelitian studi kasus asuhan komperhensif pada ibu hamil, bersalin, bayi baru lahir dan nifas ini adalah metode deskriptif. Jenis penelitian diskiptif yang digunakan adalah penelaah kasus (Case Study) sampel pada penelitian ini yaitu seorang ibu hamil trimester II usia kehamilan 27 minggu, G1P0A0. Waktu penelitian 20  Juni 2024 - 25 Oktober 2024 di wilayah Desa Jatirunggu  RT 04/RW03. Instrumen penelitian menggunakan metode dokumentassi SOAP. Pengumpulan data subjektif Ny.N mulai dari hamil, bersalin, bayi baru lahir, neonatus dan masa nifas telah dilaksanakan dan tidak terdapat kesenjangan antara teori dengan kasus. Pengkajian data objektif Ny.N mulai dari hamil, bersalin, bayi baru lahir, neonatus dan masa nifas telah dilaksanakan tidak terdapat kesenjangan antara teori dan kasus.Analisa data yang didapatkan sesuai dengan asuhan yang diberikan sehingga bisa dijadikan sebagai penegak diagnosa. Sehingga tidak ditemukan adanya kesenjangan.Penatalaksanaan asuhan kebidanan komprehensif telah dilakukan sesuai dengan kebutuhan Ny.N sehingga tidak ditemukan adanya kesenjangan antara teori dan kasus. Pendokumentasian asuhan kebidanan komprehensif telah dilaksanakan sesuai dengan manajemen SOAP